Peak Expiratory Flow Rates in Children Under 5 Years of Age. Issue 244 (December 1970) - Milner, A. D.; Ingram, D.
Abstract : An initial trial on children between 2 years 4 months and 4 years 9 months showed that good reproducible results for peak expiratory flow rates could be obtained from children over the age of 3 years using the low-range Wright Peak Flow Meter. Results on 92 normal children between the age of 3 and 5 years are reported.